INNOVATIVE APPROACHES AND FOREIGN EXPERIENCE IN MANAGING EDUCATION QUALITY - Rahimova Kutlibika Ergashevna (Modern American Journals, 2025)
This article provides information about the management system in improving the quality of education system in our society, and discusses management strucres and their significance literacy levels, and regionalcharacristics of management strategies in highereducation institutions of developed countries.
Keywords: Higher education, higher education structure, management, strategy, universities, quality of education, foreign experience.